1994
DOI: 10.1007/bf00263782
|View full text |Cite
|
Sign up to set email alerts
|

Physiological regulation of competence induction for natural transformation in Acinetobacter calcoaceticus

Abstract: Acinetobacter calcoaceticus induced competence for natural transformation maximally after dilution of a stationary culture into fresh medium. Competence was gradually lost during prolonged exponential growth and after entrance into the stationary state. Growth cessation and nutrient upshift were involved in the induction of competence. The level of competence of a chemostat culture of A. calcoaceticus was dependent on the nature of the growth limitation. Under potassium limitation a transformation frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Other groups provided evidence that the highest transformation frequencies occurred early in the exponential phase, which was consistent with rapid growth (Cruze et al ., ). The latter finding was also confirmed by several groups (Palmen et al ., , ; Porstendörfer et al ., ), who showed that natural transformation was maximally induced after the dilution of an overnight culture into fresh medium or ‘after an increase in nutrient availability, preceded by cessation of growth’ (Palmen et al ., ). In an earlier review, these contradictory findings were resolved with the conclusion that competence ‘reaches its maximum during early to late log phase in A. calcoaceticus ’ (Lorenz & Wackernagel, ).…”
Section: Environmental Cues Involved In Competence Induction In Bactementioning
confidence: 99%
See 1 more Smart Citation
“…Other groups provided evidence that the highest transformation frequencies occurred early in the exponential phase, which was consistent with rapid growth (Cruze et al ., ). The latter finding was also confirmed by several groups (Palmen et al ., , ; Porstendörfer et al ., ), who showed that natural transformation was maximally induced after the dilution of an overnight culture into fresh medium or ‘after an increase in nutrient availability, preceded by cessation of growth’ (Palmen et al ., ). In an earlier review, these contradictory findings were resolved with the conclusion that competence ‘reaches its maximum during early to late log phase in A. calcoaceticus ’ (Lorenz & Wackernagel, ).…”
Section: Environmental Cues Involved In Competence Induction In Bactementioning
confidence: 99%
“…Based on the results of a study on early competence induction, Palmen et al . () concluded that ‘the biological function of natural transformation in A. calcoaceticus is not to provide the cell with nutrients’ and that ‘the regulation of competence development as a function of the stringency of carbon, nitrogen, and phosphate limitation was just opposite to what one would expect if the ‘nutrient supply hypothesis’ would apply’.…”
Section: Environmental Cues Involved In Competence Induction In Bactementioning
confidence: 99%
“…Competent cells were prepared as before (Palmen et al, 1993(Palmen et al, , 1994 with slight modifications. Briefly, Acinetobacter sp.…”
Section: Bacterial Transformation In Liquid Mediummentioning
confidence: 99%
“…It is reasonable to suggest that different structural elements associated with transformation are expressed coordinately and function in an orchestrated manner. Interestingly, transcriptional activation of comB during the prolonged exponential growth phase does not correlate with competence development, as maximal competence is induced immediately after inoculation into fresh medium but is gradually lost during prolonged exponential growth (Palmen et al 1994;D. Porstendörfer, unpublished results).…”
Section: Discussionmentioning
confidence: 89%
“…BD413 stationary culture into fresh medium. During prolonged exponential growth competence is gradually lost until minimal transformation frequencies are reached in stationary phase (Palmen et al 1994;D. Porstendörfer, unpublished results).…”
Section: The Pilin-like Protein Comb Is Essential For Natural Transfomentioning
confidence: 88%